2003
DOI: 10.1182/blood-2002-09-2798
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 and TGF-  induce alloreactive CD4+CD25- T cells to acquire regulatory cell function

Abstract: We previously reported that interleukin-10 (IL-10) and transforming growth factor (TGF)-␤ treatment of primary mixed lymphocyte reaction (MLR) cultures resulted in secondary alloantigen-specific hyporesponsiveness and protection from graft-versus-host disease (GVHD) lethality. Here, we report that CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
115
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(119 citation statements)
references
References 36 publications
4
115
0
Order By: Relevance
“…Although prior studies show that CD4 þ CD25 À T cells can be induced into suppressing CD4 þ CD25 þ T cells by peripheral expansion, 36 we were able to demonstrate that the increase in Treg frequency was derived from natural Treg selfexpansion promoted by factors secreted by Huh7 cells and not from conversion of naïve CD4 þ CD25 À T cells. Our data also show that Huh7 supernatants and not normal hepatocyte culture supernatants inhibited PBMC proliferation in dose-dependent manner.…”
Section: Discussionmentioning
confidence: 58%
“…Although prior studies show that CD4 þ CD25 À T cells can be induced into suppressing CD4 þ CD25 þ T cells by peripheral expansion, 36 we were able to demonstrate that the increase in Treg frequency was derived from natural Treg selfexpansion promoted by factors secreted by Huh7 cells and not from conversion of naïve CD4 þ CD25 À T cells. Our data also show that Huh7 supernatants and not normal hepatocyte culture supernatants inhibited PBMC proliferation in dose-dependent manner.…”
Section: Discussionmentioning
confidence: 58%
“…Decorin, a gene product known for its potent binding capacity for transforming growth factor-h (37 -39), migration inhibitory factor (40 -43), and interleukin-1 receptor antagonist (44,45), is increased in expression in T regs from patients with glioblastoma multiforme, consistent with the premise of active inhibition of immune responses by this population of cells (15). The substantial up-regulation of decorin (up to 33-fold) may be of central importance in understanding the role of transforming growth factor-h in T reg induction and activity in these patients (46,47). Furthermore, it is interesting to note that, although not statistically significant by ANOVA, the interleukin-2 receptor was expressed at higher levels in the CD4 + and CD8 + cells of healthy volunteers compared with glioblastoma multiforme patients, whereas this receptor was expressed at lower levels in T regs from healthy volunteers compared with glioblastoma multiforme patients.…”
Section: Discussionmentioning
confidence: 85%
“…Using ELISA to detect the spontaneously released IL-10, they noted that high IL-10 production correlated with a low incidence of GVHD. Chen et al 17 reported the induction of alloantigen-specific tolerance and generation of regulatory cells by pretreatment with IL-10/TGF-b. This study also identifies IL-10-producing cells that respond to allostimulation.…”
Section: Discussionmentioning
confidence: 99%